Analisis Implementasi Pembiayaan Murabahah Berdasarkan Fatwa DSN-MUI pada PT. Bank Syariah Indonesia Tbk Periode 2023-2025 - Moh. Asep Zakariya Ansori; Roisyatin Roisyatin; Widya Yulia Nabila; Sintia Najwaludin; Siti Nuraeni Siva; Azi Febrian; Darma Trianggoro; Fajar Cahya Gumilar (As-Syirkah: Islamic Economic & Financial Journal, 2026)
This study aims to analyze the trend of sharia compliance in the implementation of murabahah financing based on the DSN-MUI Fatwa No: 04/DSN-MUI/IV/2000 and evaluate the effectiveness of the Sharia Supervisory Board (DPS) supervision at PT. Bank Syariah Indonesia Tbk (BSI) during the period 2023–2025. The methodology used is descriptive qualitative with a comparative approach through literature meta-analysis of 10 empirical studies, which are analyzed in stages at the macro (headquarters), meso (branch offices), and micro (sub-branch offices) levels. The results of the study indicate a dynamic fluctuation in compliance trends. In 2023, the implementation of murabahah in consumer products (such as KPR BSI Griya Simuda) shows very high sharia compliance and margin transparency thanks to the preventive supervision of the central DPS through standardization of legal contracts. However, significant structural challenges were identified in 2024–2025, including the practice of signing dual contracts (murabahah and wakalah simultaneously) at the branch branch level, the recognition of late fees (ta'zir) as bank income, and information asymmetry due to low public literacy. On the other hand, BSI successfully demonstrated ethical compliance in resolving problem financing through fair collateral auction procedures. This study concluded that the effectiveness of DPS supervision is significantly influenced by the disciplined integration of Sharia compliance into the bank's digital governance system.